Narrow Elastic Disposable Tourniquet (Hemaclear®) vs. Traditional wide Pneumatic Tourniquet for Creation or Revision of Hemodialysis Angioaccesses. Issue 3 (May 2016) - Bourquelot, Pierre; Levy, Bernard I.
Purpose: To choose the best arterial tourniquet for angioaccess surgery. Methods: Preventive hemostasis with an arterial tourniquet prevents bleeding and provides better visualization. The surgeon may currently use a traditional wide nonsterile inflatable pneumatic cuff after exsanguination with an Esmarch bandage or a disposable sterile narrow elastic silicone ring (HemaClear®), available in different sizes according to the patient's limb circumference and blood pressure. Results: The latter is easily rolled up the upper limb after surgical draping, to achieve exsanguination and occlusion of the proximal brachial artery, thus providing a wide sterile field that is most useful for upper arm vein superficialization or arteriovenous fistula (AVF) revision. Although rare, neurological complications must be prevented by limiting the compressive force applied to the tissues to occlude the arteries and the veins. Such tissues are almost non-compressible but deformable; thus, they may be elongated and damaged, mostly at both extremities of the tourniquet, especially the nerves. The compressive force (kg) applied to the limb by the cuff is the product of the cuff pressure (mm Hg) imposed and the surface (cm²) of the skin in contact with the cuff. Reduction of the cuff surface results in reduction of the volume of tissue beneath the cuff and therefore in limitation of the compressive force. Conclusions: From a theoretical point of view and from clinical data, it seems therefore reasonable to recommend the use of a narrower cuff size and, for practical reasons, the silicon ring.